PEMBELAJARAN MIND MAPPING DAN PROBLEM BASED LEARNING DI SMP - Ria Novitasari; Gunawan Sudarmanto; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This study aims to determine whether there are differences in the use of models of mind mapping and problem based learning on learning outcomes of students and economy to determine differences in the effectiveness of the model of mind mapping and problem based learning on economic subjects of class VII. The method used is the method of comparative research with experimental approaches. Means of collecting data in the form of achievement test of 50 multiple-choice items given to students at the beginning and at the end of the study. The first hypothesis testing using ANOVA test obtained Sig. 0.0030.05 indicate a difference in the use of models of mind mapping and problem based learning on learning outcomes of students' economy. The second hypothesis of the effectiveness of the results obtained using the formula model of mind mapping and problem based learning is 0.78 meaning that the model of problem-based learning is more effective than the model of learning mind mapping. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan penggunaan model mind mapping dan problem based learning terhadap hasil belajar ekonomi siswa dan untuk mengetahui perbedaan efektivitas model mind mapping dan problem based learning pada mata pelajaran ekonomi kelas VII. Metode penelitian yang digunakan adalah metode penelitian komparatif dengan pendekatan eksperimen. Alat pengumpul data berupa tes prestasi belajar berbentuk pilihan ganda sebanyak 50 item diberikan kepada siswa di awal dan di akhir penelitian. Pengujian hipotesis pertama menggunakan uji Anava diperoleh Sig. 0,0030,05 menunjukkan adanya perbedaan penggunaan model mind mapping dan problem based learning terhadap hasil belajar ekonomi siswa. Hipotesis kedua menggunakan rumus diperoleh hasil keefektifan model mind mapping dan problem based learning adalah 0,78 artinya model problem based learning lebih efektif dibandingkan model pembelajaran mind mapping. Kata Kunci: hasil, mm, pbl, belajar.